2020
DOI: 10.3389/fphys.2020.01001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hormonal, Metabolic, and Inflammatory Responses in CrossFit® Training: A Systematic Review

Abstract: Background: CrossFit® training is a high-intensity functional training program that aims to increase physical functional performance through biochemical responses, i.e., hormonal, metabolic, and inflammatory responses. Most hormonal, metabolic, and inflammatory changes induced by CrossFit® training have been reported in isolated clinical studies. The purpose of this review was to systematically explore the existing literature on characterization of hormonal, metabolic, and inflammatory responses res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
20
0
3
Order By: Relevance
“…The execution of the WOD is typically performed with short or no intervals between exercises and repetitions and rounds [ 3 ]. Previous studies have identified several hormonal and immune responses [ 4 , 5 ], metabolic responses [ 1 , 6 ] and cardiovascular and perceptual responses [ 6 , 7 ] after CrossFit ® workouts.…”
Section: Introductionmentioning
confidence: 99%
“…The execution of the WOD is typically performed with short or no intervals between exercises and repetitions and rounds [ 3 ]. Previous studies have identified several hormonal and immune responses [ 4 , 5 ], metabolic responses [ 1 , 6 ] and cardiovascular and perceptual responses [ 6 , 7 ] after CrossFit ® workouts.…”
Section: Introductionmentioning
confidence: 99%
“…A Capsaicina pode exercer um efeito analgésico central (CATERINA et al, 2000), o que ajuda a explicar a redução nos valores de PSEsessão encontrados no presente estudo. Tal efeito pode auxiliar, principalmente, em exercícios nos quais predominam a via anaeróbica lática, como o CrossFit (CLAUDINO et al, 2018;JACOB et al, 2020) Algumas limitações precisam ser consideradas no presente estudo: falta da análise de variáveis fisiológicas como a frequência cardíaca e produção de Lactato para correlacionar com a PSEsessão; falta de análise do desempenho dos voluntários no protocolo proposto; dificuldade em estipular um protocolo de teste para o CrossFit, uma vez que trata-se de uma modalidade com grande variações de tarefas nas competições.…”
Section: Resultsunclassified
“…O treinamento contém um conjunto de exercícios variados, com o objetivo de que todo o corpo realize esforços em um período curto de tempo, priorizando exercícios de alta intensidade e um volume maior de repetições (GLASSMAN, 2005;CLAUDINO et al 2018). Dentre a capacidades físicas exigidas, a resistência de força ou capacidade de resistir à fadiga no treinamento de força, representa um fator fundamental para o desempenho competitivo de várias modalidades esportivas, especialmente, no CrossFit (PICONI et al, 2019;JACOB et al, 2020). As competições de CrossFit são compostas por WODs, e o desempenho pode ser determinado pelo maior número de repetições realizadas no tempo preestabelecido, por exemplo (CLAUDINO et al, 2018).…”
Section: Introductionunclassified
“…The greater metabolic stress induced in a CrossFit® session may lead to exerciseinduced muscle damage (EIMD), particularly when a high volume of repetitions is performed, with EIMD being even greater if the participants are unaccustomed to the exercises performed [11]. When comparing the perceptual responses and post-exercise physical disfunction between a CrossFit® session and a session based on the guidelines of the American College of Sports Medicine, Drum et al [12] found significant differences between sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of performance and physiological markers, the perception of an athlete's readiness to perform describes a critical determinant of recovery. In this context, Laurent et al [14] proposed a perceived recovery status scale (PRS), which is similar but opposite to a perceived exertion scale (RPE) (10)(11)(12). Both scales are based on the subjective physical and mental feelings of the athlete.…”
Section: Introductionmentioning
confidence: 99%